Author Correction: Neurocognitive Correlates of Semantic Memory Navigation in Parkinson’S Disease (Npj Parkinson S Disease, 2024 10 1 15 10.1038/S41531-024-00630-4) - Chana-Cuevas, P (Nature Research, 2024)
In this article the funding from ‘Latin American Brain Health Institute (BrainLat), Universidad Adolfo Ibáñez, Santiago, Chile, #BL-SRGP2021-01’ for author Adolfo M. García was omitted. The original article has been corrected. © 2024, The Author(s).